The Effect of Core Stability Exercises Combined with Abdominal Hollowing on Postural Control Indices and Kinematic Alignment of the Lower-Limb Kinetic Chain in Female Swimmers with Chronic Nonspecific Low Back Pain - Esfandiarzadeh, Elham; Shams Kohan, Parastoo (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effect of core stability exercises combined with abdominal hollowing on postural control indices and kinematic alignment of the lower-limb kinetic chain in female swimmers with chronic nonspecific low back pain.Methods and Materials: The present study was conducted using a quasi-experimental interventional design with a pre-test and post-test approach. The statistical population included female swimmers aged 18 to 35 years participating in the Isfahan Provincial League who suffered from chronic nonspecific low back pain. Based on G*Power analysis and considering possible attrition, 25 participants were selected purposively and voluntarily. The intervention consisted of an eight-week combined core stability and abdominal hollowing training program performed three sessions per week. Data collection included assessment of pain intensity using the Visual Analog Scale, lumbar proprioception using joint position error measurement, functional disability using the Oswestry Disability Index, muscle length indices, postural alignment variables, center-of-pressure stability parameters, and dynamic balance using the Y Balance Test. Data were analyzed using descriptive statistics, repeated-measures ANOVA, and paired-samples t-tests in SPSS software at a significance level of 0.05.Findings: The findings demonstrated significant improvements in all major study variables following the intervention protocol. Pain intensity decreased significantly (F=87.63, p=0.001), lumbar proprioception error was reduced (F=69.42, p=0.001), and functional disability scores improved significantly (F=92.85, p=0.001). Significant improvements were also observed in hamstring flexibility, hip flexor length, lumbar lordosis angle, pelvic tilt, knee valgus angle, rearfoot angle, and navicular drop (p=0.001). In addition, center-of-pressure velocity, ellipse area, and directional sway parameters decreased significantly, indicating improved static postural control, while Y Balance Test scores increased significantly (F=88.94, p=0.001), reflecting enhanced dynamic balance performance. Effect sizes for most variables were large, indicating substantial clinical and biomechanical adaptations.Conclusion: The results of the present study suggest that core stability exercises combined with abdominal hollowing are effective in improving postural control, proprioception, balance, lower-limb kinematic alignment, and functional performance while reducing pain and disability in female swimmers with chronic nonspecific low back pain. The combined intervention appears to enhance neuromuscular control and optimize kinetic-chain biomechanics, making it a practical and effective rehabilitation strategy for athletic populations with chronic low back pain.